Digital adaptation issues for different demographics in Russian Moscow region - L. G. Akhmaeva; D. V. Dolgopolov; A. I. Eremeeva (Вестник университета)
The article aims to analyze the adaptation specifics of four generations to digital technologies in Russian Moscow region. The research theoretical basis consists of the basic socio-demographic generations description within the William Strauss and Neil Hove generations theory. Using methods of sociological research (polls and in-depth interviews), the article analyzes the Strauss-Hove generational theory’s actual elements in relation to the socio-demographic landscape of modern Russian society. The article considers the interaction specifics with the digital environment and gadgets for various demographic sections, as well as their involvement in modern global trends regarding Internet addiction and online positioning. The article concludes that the development of various communication channels depending on demographic targeting is required.